The gods of Prophetstown : the Battle of Tippecanoe and the holy war for the American frontier - Jortner, Adam Joseph (Oxford University Press, 2012)
It began with an eclipse. In 1806, the Shawnee leader Tenskwatawa ("The Open Door") declared himself to be in direct contact with the Master of Life, and therefore, the supreme religious authority for all Native Americans. Those who disbelieved him, he warned, "would see darkness come over the sun." William Henry Harrison, governor of the Indiana Territory and future American president, scoffed at Tenskwatawa. If he was truly a prophet, Harrison taunted, let him perform a miracle. And Tenskwatawa did just that, making the sun go dark at midday. In The Gods of Prophetstown.